A case of endogenous endophthalmitis with subretinal abscess secondary to splenic abscess. Issue 2 (April 2019) - Manoharan, Varshini; Sanghvi, Chintan
Early diagnosis and treatment of endophthalmitis will optimise visual prognosis. Blood culture sensitivities should tailor antibiotic choice.